Evaluating reliability and validity of the infant distress scale for distress assessment during and after intramuscular injection - S., Shanthi; Mendonca , Theresa Leonilda (International Journal of Contemporary Pediatrics, 2025)
The infant distress scale (IDS) was developed to assess the unpleasant feeling (distress) triggered by intramuscular injection where the child experiences pain. Numerous pain scale exists to measure pain during painful procedure, but only a few scales measuring the distress, So the investigator intended to evaluate the reliability and validity of the IDS in assessing distress both during and after intramuscular injection. The methodological research design was used to test and evaluate the research instrument. The study was conducted at an immunization clinic. Twenty infants aged between 1 to 6 months who received intramuscular vaccination were included in this study. Two observers measured the distress using separate Infant Distress Scale by observing the video recordings. In total around 120 observations were made. Face validity and content validity were established for the tool. Internal consistency of the scale was calculated using Cronbach’s alpha, with values ranging from 0.731-0.821 and the content validity index is 0.89. The study concluded that the IDS is statistically valid and reliable.